2021
DOI: 10.1080/17515831.2020.1854509
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nano-Al2O3 and PTFE fillers on tribological property of basalt fabric-reinforced epoxy composites

Abstract: Effects of nano-Al 2 O 3 and PTFE fillers on tribological behaviour of basalt fabric reinforced epoxy composite (BFRC) produced with a combination of molding and mixing method were studied by Taguchi L9 design. Microstructures and worn surfaces of composites were investigated by scanning electron microscopy. Regression equations were also developed for predicting wear and coefficient of friction. The results indicated that specific wear rate increased with increasing load and decreasing speed, but friction coe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…However, it is evident that both solid lubricants reduce the average COF when considering that COF is 0.45 for neat rigid epoxy and 0.44 for neat toughened epoxy. The positive effects of these solid lubricants on COF are supported by various researchers 12,47–50 . For example, Sahin and Patrick revealed by ANOVA that the optimum parameters for minimizing the wear rate of epoxy composites are the combinations of PTFE.…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…However, it is evident that both solid lubricants reduce the average COF when considering that COF is 0.45 for neat rigid epoxy and 0.44 for neat toughened epoxy. The positive effects of these solid lubricants on COF are supported by various researchers 12,47–50 . For example, Sahin and Patrick revealed by ANOVA that the optimum parameters for minimizing the wear rate of epoxy composites are the combinations of PTFE.…”
Section: Resultsmentioning
confidence: 89%
“…For example, Sahin and Patrick revealed by ANOVA that the optimum parameters for minimizing the wear rate of epoxy composites are the combinations of PTFE. In the same study, it was reported that reinforcement type was the second most important factor after load in wear factors 49 . In their study on the wear performance of epoxy composites, Zhang and colleagues reported that graphite reinforcements are more effective than PTFE 47 .…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Arun et al 29 and Kim et al 30 obtained results consistent with our study Sharma, 31 Pihtili and Tosun, 2 Suresha and Kumar, 32 and sahin. 33 In addition, it indicates that increasing sliding distance increased the mass loss. Since the increase in the load increased the contact pressure on the friction surfaces, it removed more chips than the adhesive abrasive composite materials.…”
Section: Resultsmentioning
confidence: 99%